The Reception of the Hermeneutical Principles of Schleiermacher and Dilthey in Hans-Georg Gadamer’s Philosophy - Gvaramadze ნინო (TSU-TI — THE INTERNATIONAL SCIENTIFIC JOURNAL OF HUMANITIES, 2024)
The reception of the two main representatives of the hermeneutical tradition of the XIX century is analyzed: Friedrich Schleiermacher and Wilhelm Dilthey - in Hans-Georg Gadamer’s Magnum Opus: "Truth and Method". I will devote the first part of this article to a review of the foundations of hermeneutics as a science in Schleiermacher’s philosophy. I show that for him, hermeneutics is a universal theory of interpretation as such, or in other words, the doctrine of the interrelationship of the rules of understanding. In the second part of the paper, I will give an overview of Dilthey’s grand methodological project. I will try to prove that the purpose of his project is to justify the importance of "Geisteswissenschaften" and to show the irreducibility of the latter’s procedures to those of “Naturwissenschaften". In the third part of the paper, I attempt to analyze how Gadamer, would rethink the Schleiermacher’s and Dilthey’s tradition. I argue that according to Gadamer, Schleiermacher sought to teach an understanding of oral and written tradition, since theology was concerned with one particular tradition, the Bible. For this reason, his hermeneutical theory was still far removed from historiography, which Gadamer believed could play the role of a methodological organon in the humanities. As for Dilthey, in Gadamerian perspective, he fails to achieve the ultimate goals he sets for hermeneutical methodology. His appeal to the natural sciences as a guide to what can be justified as true, deviates from philosophy’s more rigorous foundation as a fundamental discipline. Dilthey’s main desire to show the limits and possibilities of any kind of validity in the humanities is ultimately realized, by the fact that the humanities come much closer to the natural sciences in the scheme of appropriating the process of understanding.